(untitled) (Horizontes de Enfermería, 2018)
HIV / AIDS according to the World Health Organization (WHO) is considered a public health problem worldwide, ranking among the 10 leading causes of death in the world. Despite a treatment, adherence to antiretroviral therapy remains a major challenge for all health systems. Th e objective of this study was to determine the factors infl uencing the adherence to antiretroviral treatment in patients of the Hospital Clinical San Vicente de Paúl, in a descriptive, transverse, propositional and qualitative-quantitative design. 90 patients. Of the results obtained it is mentioned that 70% of the infected population is male, the ages comprise 20-40 years with 66.7%, sexual orientation 74.4% is heterosexual and only 15.6% MSM , 61.1% of the population studied have secondary and higher education, 17.8% are engaged in agriculture and 16.7% are public and private employees, the vast majority have a normal family function with 66, 7%, more than 95% take their medication always and at established times, 97.8% maintain a good professional / patient relationship and 52.2% take 1-5 years to receive antiretrovirals. It was concluded that factors that influence adherence are family support, educational level, professional health / patient relationship, knowledge about the disease and the advantages of retroviral therapy.